TINJAUAN HAK AKSES PEREKAM MEDIS DAN INFORMASI KESEHATAN TERHADAP DATA REKAM MEDIS ELEKTRONIK DI RUMAH SAKIT MEDIKA DRAMAGA BOGOR - Kristina, Indah; Widyaswara, Garda (MEDICORDHIF Jurnal Rekam Medis, 2024)
Medical record access rights are the use and utilization of medical records that may only be carried out by parties who have permission for medical record data in the security and protection of electronic medical record data service facility leaders grant access rights to health workers in health care facilities the purpose of this study was to determine access rights for medical recorders and health information to electronic medical record data at the medika dramaga bogor hospital. This research method uses a qualitative descriptive method with data collection techniques in the form of observation and interviews. The sample in this study were 10 medical recorders and health information.The results of the study that standard operating procedures related to access rights are available but not yet valid and signed by the leadership of the medika dramaga bogor hospital, then regarding the implementation of pmik access rights to electronic medical record data already referring to permenkes number 24 of 2022 and PMIK problems or obstacle in accessing electronic medical record data is the exchange of information between officers regarding user id and passwords which has an impact on patient data security in the event of abuse of access rights. Keywords: access rights, medical recorders and health information, electronic medical record data